2007
DOI: 10.1016/j.physa.2007.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Possible biomechanical origins of the long-range correlations in stride intervals of walking

Abstract: When humans walk, the time duration of each stride varies from one stride to the next. These temporal fluctuations exhibit long-range correlations. It has been suggested that these correlations stem from higher nervous system centers in the brain that control gait cycle timing. Existing proposed models of this phenomenon have focused on neurophysiological mechanisms that might give rise to these long-range correlations, and generally ignored potential alternative mechanical explanations. We hypothesized that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 42 publications
8
60
3
Order By: Relevance
“…To the best of our knowledge, there are no model studies relating long-range correlations to the probability of falling. However, one study [154] showed that long-range correlations are present in a fairly simple model, indicating that no complex central nervous system is needed for them to arise.…”
Section: Rsifroyalsocietypublishingorg J R Soc Interface 10: 20120999mentioning
confidence: 99%
“…To the best of our knowledge, there are no model studies relating long-range correlations to the probability of falling. However, one study [154] showed that long-range correlations are present in a fairly simple model, indicating that no complex central nervous system is needed for them to arise.…”
Section: Rsifroyalsocietypublishingorg J R Soc Interface 10: 20120999mentioning
confidence: 99%
“…Conversely, some have suggested that correlation properties are merely a by-product of the fact that feedback occurs on multiple levels or that simple biomechanical properties cause the observed scaling in gait. 144 These theories are not consistent with the observed results and the effects of various "stresses" on long-range correlation properties; the stresses do not directly change biomechanics, yet fractal scaling may be altered ͑e.g., Table II͒. 145 More specifically with regard to gait dynamics, several explanations have been put forth.…”
Section: Discussionmentioning
confidence: 89%
“…The alternative hypothesis suggested by Gates et al (2007) is that long-range correlations are due to a biomechanical filtering of the neural commands by the motor apparatus. However, the diversity of rhythmic patterns in which long-range correlation have been reported (heartbeat, saccades, spontaneous neural firing patterns, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, unstable gait has been associated with a random pattern in consecutive strides, suggesting that the loss of long-range correlation could be a precocious marker of fall risk (Hausdorff, 2007). However, Gates et al (2007) suggested that the long-range correlation in gait could result from white noise fluctuations in the neural motor commands that are somehow filtered by the biomechanical plant, and this remains an open question. Thus, the development of reliable methods for quantifying and analyzing the correlation function in physiological time series is essential for both fundamental and clinical applications.…”
Section: Introductionmentioning
confidence: 99%